PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, CSR, PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA SAHAM LQ 45 YANG TERDAFTAR DI BEI - Alya Rana Tsabita (2023)
This research was conducted to test and prove the effect of independent commissioners, audit committees, corporate social responsibility (CSR) and company growth on firm value with firm size and leverage as control variables. This research focuses on lq45 index stock companies in 2018-2022. The sample in this research is 170 data samples selected by purposive sampling method. This research includes a secondary quantitative type. Random Effect Model (REM) with multiple linear regression used in this study using STATA13 MP (64-bit). The significance level used is 5%. The results of the study show that: 1) independent commissioners have a significant positive effect on firm value; 2) the audit committee has a significant negative effect on firm value; 3) corporate social responsibility (CSR) has no significant effect on firm value; 4) firm growth has no significant on firm value; 5) firm size and leverage as control variables do not have a significant effect on firm value.